FAMILY CHALLENGES AND COPING MECHANISMS DURING THE COVID-19 PANDEMIC: WESTERN CAPE, SOUTH AFRICA - Kader, Zainab; Benjamin, Fatiema; Manuel, Donnay Anthea; Mpilo, Mulalo; Titus, Simone; Roman, Nicolette V. (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
The COVID-19 pandemic has impacted the health and well-being of families in South Africa, amplifying family challenges and requiring modifications to their coping mechanisms. While the pandemic has been successfully managed in South Africa, some challenges, such as those related to poverty, loss of income, and economic uncertainty, have been exacerbated. This study, which used an exploratory qualitative research design, sought to offer insight into the coping mechanisms of South African families used to deal with family challenges during the pandemic. Through purposive and snowball sampling, 31 participants were recruited; the majority were living in a nuclear family, but some had other arrangements. The participants were from six municipal districts in the Western Cape Province. Semi-structured interviews were conducted, and data were analysed using thematic analysis. The findings of this study demonstrate that the coping mechanisms families used during the COVID-19 pandemic were largely drawn from internal resources.